2007
DOI: 10.1002/pc.20241
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics for fiber volume percent with a photocure vinyl ester composite

Abstract: Micromechanics for fiber volume percent () from 0.0 to 54.0 were conducted using (3 mm long × 9 µm diameter) high-purity quartz fibers in a visible-light vinyl ester particulate-filled photocure resin. MTS fully articulated four-point bend fixtures were used with a 40 mm test span and 50 × 2 × 2 mm sample dimensions. Specimens were tested following the combined modified ASTM standards for advanced ceramics ASTM-C-1161-94 and polymers ASTM-D-6272-00 for modulus, flexural strength, and yield strength. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…5. A similar increase in FT (from 1.7 to 4.6 MPa m 1/2 ) was reported by Petersen et al [32] when 5.4 vol% of highly oriented 3-mm fibers replaced zirconia particles in a 66 vol% filled composite. Studies reporting FT of fiber-reinforced composites are not numerous.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…5. A similar increase in FT (from 1.7 to 4.6 MPa m 1/2 ) was reported by Petersen et al [32] when 5.4 vol% of highly oriented 3-mm fibers replaced zirconia particles in a 66 vol% filled composite. Studies reporting FT of fiber-reinforced composites are not numerous.…”
Section: Discussionsupporting
confidence: 81%
“…It is possible that, relatively to filler particles, fiber fraction was too low to have a significant effect on strength. In fact, Petersen et al [32] reported substantial increases in FS when highly oriented short fibers replaced zirconia silicate fillers in volume fractions between 10.3% and 54%. Moreover, the reduction in strength observed with the composite containing 5% of fibers suggests two concurring effects.…”
Section: Discussionmentioning
confidence: 96%
“…12. The ability to pack or condense particulate-filled composite is retained by securing intermolecular forces of attraction between the high viscosity BisGMA photocure resin that are assumed to be by hydrogen bonding [Esstech, Inc., 2013a; Esstech, Inc., 2013b] and further by interparticle van der Waals forces of attraction particularly for the smaller nanosize particulate [Milewski, 1973; Atkins, 1994; Petersen, 2006; Petersen et al ., 2007a]. …”
Section: Discussionmentioning
confidence: 99%
“…Practical knowledge for the dominating constituents of a composite structure has clearly demonstrated that structural mechanical strength-type properties are influenced most highly by fibers [Chawla, 1998; Peters, 1998; Petersen and Wenski, 2002; Petersen, 2005; Petersen et al ., 2006; Petersen et al ., 2007a; Petersen et al ., 2007b]. Regarding highly relevant biological interactions, conducting carbon fibers that reinforce developmental biopolymer implants have influenced enhanced cell growth beyond normal limits [Petersen, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…A tougher, less brittle composite then aids in making thinner parts [12] which becomes more important for small biomedical devices. In addition, polarized inorganic fillers similar to bone mineral are commonly included in thermoset free-radical cure bisphenyl polymers to improve mechanical/physical properties and control manufacturing process consolidation [2, 13, 14]. Eukaryote mammalian cells then extensively require inorganic calcium and phosphates derived from a large bone source to insulate and seal lipid membrane compartments and establish voltage potentials [15-17].…”
Section: Introductionmentioning
confidence: 99%